Temporal Association between Federal Gun Laws and the Diversion of Guns to Criminals in Milwaukee - Webster, Daniel W. (Springer US, 2012)
The practices of licensed gun dealers can threaten the safety of urban residents by facilitating the diversion of guns to criminals. In 2003, changes to federal law shielded gun dealers from the release of gun trace data and provided other protections to gun dealers. The 14-month period during which the dealer did not sell junk guns was associated with a 68% reduction in the diversion of guns to criminals within a year of sale by the dealer and a 43% increase in guns diverted to criminals following sales by other dealers. The laws were associated with a 203% increase in the number of guns diverted to criminals within a year of sale by the gun store, which was the focus of this study. Policies which affect gun dealer accountability appeared to influence the diversion of guns to criminals.